Behavioral Changes Under Levetiracetam Treatment in Dogs - Erath, Johannes Roland; Nessler, Jasmin Nicole; Riese, Franziska; Hünerfauth, Enrice; Rohn, Karl; Tipold, Andrea (Frontiers in Veterinary Science, 2020)
In veterinary medicine levetiracetam is a well tolerated antiepileptic drug (AED) with only mild to moderate side effects. Behavioral changes are rare in animals. In contrast, in human medicine the impact of levetiracetam on behavior was frequently described. Since in the Clinic for Small Animals at the University of Veterinary Medicine Hannover single canine patients were observed with behavioral abnormalities after levetiracetam treatment, the following hypothesis was generated: Levetiracetam induces behavioral changes or causes an intensifying of pre-existing behavioral abnormalities in dogs with seizures. In this monocentric study 84 client-owned dogs with recurrent seizures receiving levetiracetam as monotherapy, add on treatment or pulse therapy met inclusion criteria. The behavior of the dogs before and after levetiracetam treatment was ascertained using validated questionnaires. Fourty-four dogs already developed changes in their behavior during the disease without levetiracetam application. After levetiracetam administration, these behavioral changes were intensified in 14/44 dogs and 4/44 dogs developed at least one additional negative behavioral abnormality in comparison to their behavioral state before treatment. In 10/40 dogs without pre-existing behavioral abnormalities, newly observed behavioral traits were noticed (e.g. anxiety, aggression). The changes already occurred after the first application in five of these ten dogs. Levetiracetam was administered as pulse (7/10) or long-term therapy (3/10). Behavioral changes were reversible in 5/10 dogs. 15 of all 84 examined dogs developed positive behavioral changes under treatment (e.g. increased energy). In conclusion, positive and negative behavioral changes under levetiracetam treatment occur in dogs. Pre-existing behavioral problems should be taken into account, when deciding for levetiracetam treatment and potential intensifying or change in the dogs` behavior should be discussed with the owners.